Methodological considerations concerning the use of length frequency analysis for growth studies in the Norway lobster, Nephrops norvegicus (L.) - Castro, Margarida; Mytilineou, Chryssi; Gancho, Paula (Scientia Marina, 1998)
The structure of length distributions of Nephrops norvegicus was investigated in order to understand the adequacy of length frequency analysis for estimation of growth rates and growth parameters. Samples from two areas were used: the Atlantic Ocean off the South coast of Portugal and the Euboikos Gulf in the Mediterranean. Monthly samples were obtained from October 1993 to October 1995. For each area, month and sex, the samples were analyzed using the program MIX in order to identify the mean length for each of the groups composing the length distributions. The mean values were used to estimate increments between consecutive groups within the same sample. Biological information extracted from the same samples and referring to maturation and molting cycles, was used in conjunction with the mean values estimated in this work to interpret modal progression and growth rates. Results show that modal progression analysis is not appropriate because the modes do not progress in a manner that allows the following of a particular group. Growth rates based on increments verified within each sample were also investigated. This approach proved to be better, although there were still some problems due to large year to year variability and the fact that the magnitude of the increments did not decrease with increasing size. This also poses problems regarding the fitting of growth curves to these data; in particular when deceleration of growth is required, as in the case of the von Bertalanffy growth curve.